An MSN-PEG-IP drug delivery system and IL13Rα2 as targeted therapy for glioma. Issue 26 (26th April 2017) - Shi, Jinlong; Hou, Shiqiang; Huang, Jianfei; Wang, Shanshan; Huan, Wei; Huang, Chuanjun; Liu, Xiaojiang; Jiang, Rui; Qian, Wenbo; Lu, Jingjing; Wang, Xiubing; Shi, Wei; et al.
Abstract : A combination of gene therapy and chemotherapy has recently received interest as a targeted therapy for glioma. Abstract : A combination of gene therapy and chemotherapy has recently received interest as a targeted therapy for glioma. A mesoporous silica nanoparticle (MSN)-based vehicle coated with IL13Rα2-targeted peptide (IP) using polyethylene glycol (PEG), MSN-PEG-IP (MPI), was constructed and confirmed as a potential glioma-targeted drug delivery system in vitro . In this work, tissue microarray (TMA) results revealed that IL13Rα2 was over-expressed in human glioma tissues and that high expression of IL13Rα2 in patients was associated with poor survival. Doxorubicin (DOX)-loaded MPI (MPI/D) crossed the blood–brain barrier, specifically targeting glioma cells and significantly enhancing the cellular uptake of DOX in glioma cells compared with MSN/DOX (M/D) and MSN-PEG/DOX (MP/D), whereas the normal brain was not affected. Magnetic Resonance Imaging (MRI) examinations showed that the tumour size of glioma-bearing rats in the MPI/D-treated group was much smaller than those in the M/D and MP/D treated groups. Immunofluorescence results demonstrated that MPI/D treatment induced more apoptosis and much less proliferation than the other two treatments. However, the therapeutic effect was weak when IL13Rα2 was knocked down. Furthermore, U87 cells treated with IL-13 and MPI together could increase both STAT6 and P63 expression, which attenuated glioma cell proliferation, invasion and migration compared with cells treated with IL-13 alone. The results of the subcutaneous tumour model also revealed that IL13Rα2 knockdown could hinder cell proliferation and induce more apoptosis. The promising results suggested that MPI can not only deliver DOX to glioma in a targeted manner but also occupy IL13Rα2, which can promote IL-13 binding to IL13Rα1 and activation of the JAK-STAT pathway to induce an anti-glioma effect.